Informal caregiving and the risk of material hardship in the United States. (7th October 2021) - Campbell, Colin; Walker, Jasmine
Abstract: Millions of people in the United States provide unpaid care to family and friends with long‐term illnesses and disabilities. Research shows that informal caregiving can be beneficial for recipients of care, but taxing for those providing care. Studies have not explored associations between informal caregiving and the risk of experiencing different forms of material hardship. In this study, we use data from the Survey of Income and Program Participation ( N = 31, 633) to address this gap in the literature. The sample was drawn from a multistage‐stratified sample of the civilian, non‐institutionalised population of the United States. We analyse data that were collected in 2011 and find that providing informal care to others is associated with an increased risk of experiencing healthcare hardship, bill‐paying hardship and food insecurity. Moreover, we find that household financial resources mediate the association between caregiving and material hardship. As a result, while caregiving households face a higher risk of experiencing material hardships at all income levels, the disparity is largest at low incomes and smallest at high incomes. The findings highlight the need for a stronger safety net for informal caregivers.